2006
DOI: 10.1111/j.1747-0765.2006.00065.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the application of charred bark ofAcacia mangiumon the yield of maize, cowpea and peanut, and soil chemical properties in South Sumatra, Indonesia

Abstract: Charred bark of Acacia mangium (bark charcoal), which is made of wood waste from pulp production, was applied as soil amendment for the cultivation of maize, cowpea and peanut to examine its effects on crop yield and soil chemical properties in South Sumatra, Indonesia. The yields of maize and peanut significantly increased after the application of bark charcoal under a fertilized condition in an infertile soil environment. In addition, increases in the root amount and colonization rate of arbuscular mycorrhiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
294
3
21

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 570 publications
(343 citation statements)
references
References 14 publications
25
294
3
21
Order By: Relevance
“…These experiments show that additions of biochar materials generally result in the alteration of soil physico-chemical properties that may lead to increases in soil nutrient availability (measurements taken from both soil samples and plant tissues) and/or increases in root colonization by mycorrhizal fungi (Ishii and Kadoya 1994;Matsubara et al 2002;Yamato et al 2006). In a greenhouse experiment by Matsubara et al (2002), the soil pH of treatments receiving biochar increased from 5.4 to 6.2 (10% biochar by volume) and 6.3 (30% biochar by volume).…”
Section: Mechanism 1: Biochar Changes Soil Nutrient Availabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…These experiments show that additions of biochar materials generally result in the alteration of soil physico-chemical properties that may lead to increases in soil nutrient availability (measurements taken from both soil samples and plant tissues) and/or increases in root colonization by mycorrhizal fungi (Ishii and Kadoya 1994;Matsubara et al 2002;Yamato et al 2006). In a greenhouse experiment by Matsubara et al (2002), the soil pH of treatments receiving biochar increased from 5.4 to 6.2 (10% biochar by volume) and 6.3 (30% biochar by volume).…”
Section: Mechanism 1: Biochar Changes Soil Nutrient Availabilitymentioning
confidence: 99%
“…Increases in soil pH towards neutral values (Lucas and Davis 1961), in addition to increased CEC (Glaser et al 2002), may result in increases in bio-available P and base cations in biochar influenced soils. Additionally, Lehmann et al (2003), Topoliantz et al (2005), Gundale and DeLuca (2006) and Yamato et al (2006) showed that biochar itself contained small amounts of nutrients that would be available to both soil biota (including mycorrhizal fungi) and plant roots. Lastly, DeLuca et al (2006) showed that biochar from forest wildfire stimulated gross and net nitrification rates, most likely mediated by biochar adsorbing inhibitory phenols.…”
Section: Mechanism 1: Biochar Changes Soil Nutrient Availabilitymentioning
confidence: 99%
“…Another research group reported the changes in the chemical properties of soil and crop yields with the application of bark charcoal of Acacia mangium made from bark waste from a pulp factory (Yamato et al 2006). The charcoal was applied as a soil amendment for the cultivation of maize, cowpea, and peanut in Sumatra, Indonesia.…”
Section: Rice Husk Charcoalmentioning
confidence: 99%
“…Biochar amendment on soil may have agronomic advantages, including improvements in soil quality and plant growth (Jeffery et al, 2011;Chan et al, 2008). Biochar has been reported to increase both (Chan et al, 2008;Yamato et al, 2006), as well as decrease (Deenik et al, 2010) plant growth, but there was little evidence to support the hypothesis of increased seed germination with the addition of biochar. Researchers observed species-dependent effects of biochar on the germination (Free et al, 2010;Keller et al, 2010;Kwapinski et al, 2010;Van Zwieten et al, 2010;Solaiman et al, 2011;Robertsonet et al, 2012;Kamara et al, 2014;Soni, et al, 2014).…”
Section: Introductionmentioning
confidence: 66%